Genome-Wide Identification and Expression Analysis of the Biotin Carboxyl Carrier Subunits of Heteromeric Acetyl-CoA Carboxylase in Gossypium - Cui, Yupeng; Zhao, Yanpeng; Wang, Yumei; Liu, Zhengjie; Ijaz, Babar; Huang, Yi; Hua, Jinping (Frontiers in Plant Science, 2017)
Acetyl-CoA carboxylase is an important enzyme, which catalyzes acetyl-CoA's carboxylation to produce malonyl-CoA and to serve as a committed step for de novo fatty acid biosynthesis in plastids. In this study, 24 putative cotton BCCP genes were identified based on the lately published genome data in Gossypium. Among them, 4, 4, 8 and 8 BCCP homologs were identified in Gossypium raimondii, G. arboreum, G. hirsutum and G. barbadense, respectively. These genes were divided into two classes based on a phylogenetic analysis. In each class, these homologs were relatively conserved in gene structure and motifs. The chromosomal distribution pattern revealed that all the BCCP genes were distributed equally on corresponding chromosomes or scaffold in the four cotton species. Segmental duplication was a predominant duplication event in both of G. hirsutum and G. barbadense. The analysis of the expression profile showed that 8 GhBCCP genes expressed in all the tested tissues with changed expression levels, and GhBCCP genes belonging to class II were predominantly expressed in developing ovules. Meanwhile, the expression analysis for the 16 cotton BCCP genes from G. raimondii, G. arboreum and G. hirsutum showed that they were induced or suppressed by cold or salt stress, and their expression patterns varied among different tissues. These findings will help to determine the functional and evolutionary characteristics of the BCCP genes in Gossypium species.